1996
DOI: 10.1111/j.1398-9995.1996.tb04495.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergy to foods in patients monosensitized to Artemisia pollen

Abstract: A. Allergy to foods in patients monosensitized to Artenzisia pollen.Allergy 1996: 51: 927-931. 0 Munksgaard 1996. It is known that patients with pollinosis may display clinical characteristics caused by allergy to certain fruits and vegetables, but subjects allergic to Avteniisia seem to show particularly peculiar characteristics. The clinical features of 84 patients with rhinitis, asthma. urticaria, and/or anaphylaxis whose inhalant allergy was exclusively to Arteniisia vulgaris were studied and compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 16 publications
3
12
0
1
Order By: Relevance
“…Some previous papers deal with the possible association between carrot and lettuce sensitization [1,2,4,10], however, like in previous studies [1] we did not find any IgE binding band at 17-18 kDa, the molecular weight of the most reactive carrot allergen [1,20]. It was also an evidence against such association that the studied patient did not present clinical or diagnostic positivity to carrot.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Some previous papers deal with the possible association between carrot and lettuce sensitization [1,2,4,10], however, like in previous studies [1] we did not find any IgE binding band at 17-18 kDa, the molecular weight of the most reactive carrot allergen [1,20]. It was also an evidence against such association that the studied patient did not present clinical or diagnostic positivity to carrot.…”
Section: Discussionsupporting
confidence: 64%
“…Not many cases of systemic adverse reactions after lettuce intake have been described in the literature [1][2][3][4], although it has been reported as cause of occupational contact dermatitis [3,[5][6][7][8][9][10]. In fact, lettuce has been included in an important number of hypoallergenic diets [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 84 patients monosensitized to Artemisia, 11 (13%) reported symptoms to sunflower seed ranging from OAS to anaphylaxis (14). A similar presentation was reported in a patient with mugwort sensitization who developed anaphylaxis after consuming a meal containing sunflower oil (85).…”
Section: Sunflower Seed Cross-reactivitymentioning
confidence: 73%
“…Scattered case reports suggest that allergy to sunflower seed is not as common (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Sunflower seeds are commonly used as bird feed, and in some cases, the first reaction following ingestion was preceded by sensitization through handling, reflecting a role by skin contact or inhalation (12,13,15).…”
Section: Anaphylaxis and Other Ige-mediated Reactions By Ingestionmentioning
confidence: 99%